Innovation, economic diversification and human development - Dominik Hartmann; Andreas Pyka (Universität Hohenheim, Forschungszentrum Innovation und Dienstleistung (FZID), 2013)
In this paper we bridge a gap between innovation economics and the human development approach by analyzing positive and negative effects of different types of economic diversification on social welfare. Economic variety is a driver and outcome of economic development. However, diversification leads to ambiguous effects on the well-being of human agents: on the one hand, increasing variety augments the freedom of human agents to choose. On the other hand, it can overburden their capabilities to make economic decisions and can deteriorate their well-being. It becomes clear that human development policy has to go hand in hand with an industrial policy that promotes qualitative economic diversification. Depending on its dynamics, this diversification can be achieved via related and unrelated variety. We can expect a better design of development policies from a better understanding of the co-evolutionary development of variety, freedom of choice and well-being.
urn:nbn:de:bsz:100-opus-8182
Keywords: O10; O54; E11; 330; innovation; economic diversification; human development